Intertwined Sources of Buddhist Modernist Opposition to Ritual: History, Philosophy, Culture - Payne, Richard K. (Religions, 2018)
This essay is an inquiry into the religio-cultural background of the opposition to ritual evidenced by many adherents of Buddhist modernism. This background can be structured by three different kinds of questionshistorical, philosophical, and cultural.